Pengaruh Model Discovery Learning Berbantuan Team Assisted Individualization (TAI) terhadap Keterampilan Diskusi dan Komunikasi pada Materi Ekosistem - Astuti Putri Wiji Handayani; Nurmiyati Nurmiyati; Umi Fatmawati (Universitas Sebelas Maret, 2025)
This study aims to know the effect of discussion and communication skills of grade X students through the application of discovery learning and discovery learning models integrated with Team Assisted Individualization (TAI) on ecosystem material. The study used a quantitative approach with a pseudo-experimental design and cluster random sampling technique. Data were collected through observation, interviews, and documentation, then processed using SPSS 25 with normality, homogeneity, hypothesis, and further tests. The results showed that there was a significant effect of TAI-based discovery learning model on students' discussion skills with probability values of 0.011 and 0.032 (p < 0.05), and on communication skills with probability values of 0.042 and 0.003 (p < 0.05). Multivariate analysis proved the simultaneous effect on both skills compared to the conventional discovery learning group with a probability value of 0.001 (p < 0.05). Based on the research results indicate that the TAI integration discovery learning models have influence to ward student discussion and students communication ecosystem learning.